AMBIGUITAS DALAM UU RI NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA - Tria Putri Mustika; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study, entitled The ambiguity in the Act No. 39 of 1999 on Human Rights. This study aimed to describe the types of indicators causes ambiguity and ambiguities contained in Law No. 39 of 1999 on Human Rights. The research is a qualitative research with descriptive methods. Data of this study are the verses contained in Law No. 39 of 1999 on Human Rights. The results of the research I have found in this study is in Law No. 39 of 1999 on Human Rights, there is a paragraph that is ambiguous, with the kind of level of grammatical ambiguity at the level of morphological and grammatical ambiguity at the level syntactic level. Among the types of ambiguity, ambiguous dominant contained in Law No. 39 of 1999 on Human Rights is the kind of level of grammatical ambiguity at the level of syntax. Ambiguities contained in Law No. 39 of 1999 on Human Rights of which cause for reference are not clear, the composition of the structure of phrases and sentences, and polysemy.Key words: ambiguity, the Law on Human Rights, the type of ambiguity, the indicators cause ambiguity.